Global action on the social determinants of health. (1st December 2017) - Donkin, Angela; Goldblatt, Peter; Allen, Jessica; Nathanson, Vivienne; Marmot, Michael
Abstract : Action on the social determinants of health (SDH) is required to reduce inequities in health. This article summarises global progress, largely in terms of commitments and strategies. It is clear that there is widespread support for a SDH approach across the world, from global political commitment to within country action. Inequities in the conditions in which people are born, live, work and age, are however driven by inequities in power, money and resources. Political, economic and resource distribution decisions made outside the health sector need to consider health as an outcome across the social distribution as opposed to a focus solely on increasing productivity. A health in all policies approach can go some way to ensure this consideration, and we present evidence that some countries are taking this approach, however given entrenched inequalities, there is some way to go. Measuring progress on the SDH globally will be key to future development of successful policies and implementation plans, enabling the identification and sharing of best practice. WHO work to align measures with the sustainable development goals will help to forward progress measurement.